EP 126. Virtual Reality in the assessment of a manual bias towards food. Issue 9 (September 2016) - Schroeder, P.A.; Lohmann, J.; Butz, M.V.; Plewnia, C.
Abstract : Biased attentional and cognitive processes are documented for various psychiatric conditions, mostly linked with illness-specific stimuli. Prominent cognitive bias modification paradigms aim at addressing specific cognitive-behavioral deviations and corroborate therapy outcomes. Interestingly, because bodily and motivational tendencies might contribute to biased behavior, actual movements are starting to be included in bias modification paradigms in the form of approach-avoidance trainings (Wiers et al., 2011 ). Here, we introduce a novel experimental setup in Virtual Reality to include actual hand ward and grasp movements in manual interactions with critical stimuli (Fig. 1 ). The aim of this study was to identify motor contributions to the attentional bias towards food, a well-established finding. First, an attentional bias towards food was replicated during the course of grasping 3D objects of palatable objects as compared to ball objects. Food objects were collected faster than ball objects and the difference increased with larger body-mass indices of the healthy subjects (Schroeder et al., 2015 ). This finding was replicated in a larger sample, but the behavioral bias towards food was driven by high-calorie food objects exclusively, as compared to 3D objects of balls, office objects, and low-calorie fruits, crucially. Exploratory analyses of the hand movement trajectories are presented and we discuss the implications for and limitations of the use of Virtual Reality in the assessment of biased behavior. An embodied perspective on the development and maintenance of biased cognitive processing may opt further therapeutic applications of (full-) body tracking technologies and may suggest the involvement of motor regions in addition to a fronto-limbic network.